A new species of Ormosia (Leguminosae, Papilionoideae, Sophoreae) from the Brazilian Atlantic Rain Forest - Meireles, Jose Eduardo; de Lima, Haroldo Cavalcante (Phytotaxa, 2013)
A new legume species from the Brazilian Atlantic Rain Forest, Ormosia altimontana, is described and illustrated. The new species belongs to the section Ormosia, series Excelsae, and shows morphological affinities with O. friburgensis and O. ruddiana, from which it is distinguished by having fewer leaflets (5-7) with prominent secondary veins, a tomentose abaxial surface, and longer pulvinules, and slightly longer flowers. A Principal Component Analysis of vegetative morphometric data supports O. altimontana as morphologically distinct from O. friburgensis and O. ruddiana.